Optimisasi Katekese Digital: Pemberdayaan Mahasiswa Katekis dalam Evangelisasi Baru - Emmeria Tarihoran; Antonius Denny Firmato (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2024)
This research explores efforts to empower Catechist students in facing the challenges of the digital age, focusing on developing blessing skills through a digital catechesis approach. This study used qualitative methods and phenomenological approaches to involve Catechist students as the main participants. The program